Toward hydrogen economy in Kazakhstan - Saule Zholdayakova; Yerdaulet Abuov; Daulet Zhakupov; Botakoz Suleimenova; Alisa Kim (Asian Development Bank Institute (ADBI), 2022)
The energy transition is driving governments and industries to adopt various measures to reduce their climate impacts while maintaining the stability of their economy. Hydrogen technologies are one of the central topics in the energy transition. Different nations have different stances on it. Some governments see hydrogen as a decarbonization tool or part of their energy security strategy, while some others see it as a potential export commodity. While identifying priorities for the future, Kazakhstan should clearly define the role of hydrogen in the country's long-term energy and decarbonization strategy. This work presents the first country-scale assessment of hydrogen technologies in Kazakhstan by focusing on policy, technology and economy aspects. A preliminary analysis has shown that Kazakhstan should approach hydrogen mainly as a part of its long-term decarbonization strategy. While coping with the financial risks of launching a hydrogen economy, the country can benefit from the export potential of low-carbon hydrogen in the near term. The export potential of low-carbon hydrogen in Kazakhstan is justified by its proximity to the largest hydrogen markets, huge resource base, and potentially low cost of production (in the case of blue hydrogen). Technology options for hydrogen transportation and storage for Kazakhstan are discussed in our work. The paper also identifies target hydrogen utilization areas in emission sectors regulated by Kazakhstan's Emissions Trading System.
Keywords: L52; L71; Q42; 330; hydrogen roadmap; hydrogen strategy; blue hydrogen; green hydrogen; hydrogen export; metal hydrides